Prevalence and influencing factors of anxiety and depression symptoms among surgical nurses during COVID‐19 pandemic: A large‐scale cross‐sectional study - Chunxia Ren; Decun Zhou; Yinguang Fan; Baozhu Li; Wanfei Zhang; Yun Shen; Shihui Yu; Li Jiang; Fengqiong Yu; Yongli Duan; Deqing Peng; Xuehong Cheng; et al. (Wiley, 2022)
Abstract Aim To evaluate the prevalence and influencing factors of anxiety and depression symptoms in surgical nurses during the COVID‐19 epidemic in Anhui, China. Methods A cross‐sectional, multic'entre quantitative study was conducted among surgical nurses in Anhui province. SAS, SDS and SSRS scales were used for the investigation. Data were collected between 3 March 2020 to 19 March 2020. Results A total of 3,492 surgical nurses completed the survey. The average level of anxiety and depression of surgical nurses were higher than that of the Chinese norm. Levels of social support for surgical nurses were significantly negatively associated with the degree of anxiety and depression. Fertility status, participation in care for COVID‐19 patients, likelihood of being infected with COVID‐19 and social support were significantly influencing surgical nurses' anxiety degree. Similarly, these characteristics were significantly associated with the odds of depression symptoms in surgical nurses. Conclusion These findings suggest that targeted psychological interventions to promote mental health of surgical nurses need to be immediately implemented.